A high-throughput Galectin-9 imaging assay for quantifying nanoparticle uptake, endosomal escape and functional RNA delivery - Michael J. Munson (Nature Portfolio, 2021)
Munson et al. develop a high-throughput Galectin-9 reporter based endosomal escape imaging assay to probe correlations between nanoparticle-mediated uptake, endosomal escape frequency, and mRNA translation. By screening various delivery systems, modulators and combinations of nanoparticle components, the authors demonstrate how nanomedicines can be optimized for superior escape properties and efficacy in specific applications.